(untitled) (Eurasian Research Bulletin, 2023)
This article presents the current issues of increasing the level of capitalization and strengthening the financial stability of commercial banks. In addition, the amount and dynamics of the capital of commercial banks of our republic, the share of the authorized capital in their own funds, and the state of indicators describing their level of capitalization were analyzed and conclusions were given.